The Theory of Planned Behavior Approach to Public Accounting Firm Selection Decisions: A Behavioral Accounting Perspective Analysis - Noviansyah Rizal (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to empirically examine the influence of the professional service marketing mix (personal selling, direct selling, and advertising) on ​​corporate decisions regarding the selection of Public Accounting Firms (PAFs), utilizing a behavioral accounting approach. Employing a quantitative method with multiple linear regression analysis, data were collected from 100 corporate financial decision-makers in East Java. Partial analysis results indicate that personal selling has a positive and significant impact on the decision to select a PAF. Conversely, direct selling and advertising do not show a significant partial effect. However, when analyzed simultaneously, the three variables significantly influence the decision to select PAF services, with a coefficient of determination (R-squared) of 28.5%. Personal selling was identified as the most dominant behavioral determinant. These findings confirm behavioral accounting theory and the Theory of Planned Behavior, demonstrating that in the high-risk audit service industry, interpersonal interaction and direct trust are far more crucial to management psychology than rigid mass promotion strategies.